2017
DOI: 10.1155/2017/7390516
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Effects of Maternal Deprivation on Redox Regulation in Rat Brain: Involvement of NADPH Oxidase

Abstract: Maternal deprivation (MD) causes perinatal stress, with subsequent behavioral changes which resemble the symptoms of schizophrenia. The NADPH oxidase is one of the major generators of reactive oxygen species, known to play a role in stress response in different tissues. The aim of this study was to elucidate the long-term effects of MD on the expression of NADPH oxidase subunits (gp91phox, p22phox, p67phox, p47phox, and p40phox). Activities of cytochrome C oxidase and respiratory chain Complex I, as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 65 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…This is particularly pertinent to parvalbumin-expressing neurons, which are known to downregulate parvalbumin expression upon oxidative stress and in schizophrenia patients (Akbarian et al, 1995 ; Schmalbach et al, 2015 ; Janickova and Schwaller, 2020 ). Our previous work has shown that MD rats have indeed increased levels of oxidative stress, as well as higher numbers of microglial cells in the hippocampus (Marković et al, 2017 ). Another possible interpretation of our results would be that degeneration and loss of interneurons occur at the later stage, between 15 and 60 days of age.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This is particularly pertinent to parvalbumin-expressing neurons, which are known to downregulate parvalbumin expression upon oxidative stress and in schizophrenia patients (Akbarian et al, 1995 ; Schmalbach et al, 2015 ; Janickova and Schwaller, 2020 ). Our previous work has shown that MD rats have indeed increased levels of oxidative stress, as well as higher numbers of microglial cells in the hippocampus (Marković et al, 2017 ). Another possible interpretation of our results would be that degeneration and loss of interneurons occur at the later stage, between 15 and 60 days of age.…”
Section: Discussionmentioning
confidence: 94%
“…It is conceivable that stress during this vulnerable time in cortical circuitry development increases apoptotic cell death of supernumerous interneurons, which is also at its peak during the second week of postnatal development (Blomgren et al, 2007 ; Schmid et al, 2013 ). Furthermore, we cannot exclude the possibility that PV immunoreactivity loss is caused by oxidative stress or neuroinflammation (Francis and Stevenson, 2011 ; Holland et al, 2014 ; Schmalbach et al, 2015 ; Marković et al, 2017 ). Our finding of decreased parvalbumin expression is consistent with the results of earlier studies showing reduced PV expression and cell density in the prefrontal cortex of the adolescent, but not adult (P100) rats (Francis and Stevenson, 2011 ; Wieck et al, 2013 ; Holland et al, 2014 ; Grassi-Oliveira et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although interconnected with what is generally considered to be the stress response system centered on the hypothalamic-pituitary-adrenal axis, oxidative stress is a largely cellular process (Schiavone, Jaquet, Trabace, & Krause, 2013). Social stressors relevant to personality disorder, such as maternal deprivation, social defeat, and social deprivation, have been found to increase oxidative stress (Markovic et al, 2017;Schiavone et al, 2009;Solanki, Salvi, Patki, & Salim, 2017). We have previously found that impulsive aggression and the presence of personality disorder are both associated with increased oxidative stress, as evidenced by elevated blood levels of 8-hydroxy-2'-deoxyguanosine (8-OH-DG; Coccaro, Lee, & Gozal, 2016).…”
mentioning
confidence: 99%
“…Experimental models of early-life stress have already been associated with alterations on oxidative status and, thus, reported associations between altered mitochondrial respiratory chain, increased neuronal damage, decreased neuronal population in the hippocampus and impairments in spatial memory (Marković et al 2017;Noschang et al 2010;Zhu et al 2004). These impairments can be associated with the fact that the hippocampus is a susceptible region to both behavioral early life alterations and the effects of oxidative stress (Huang 2014;Salim 2017;Wang and Michaelis 2010;Youssef et al 2019).…”
Section: Introductionmentioning
confidence: 99%